Enhancement of the luminescence properties of Sr3(PO4)2:Dy3+, Li+ white‐light‐emitting phosphors by charge compensator Li+ co‐doping. (8th September 2017) - Li, Yuhang; Dai, Siyi; Zhang, Wentao; Zhang, Peicong; Qiu, Kehui
Abstract: Sr3 (PO4 )2 :Dy 3+, Li + phosphors were prepared using a simple high temperature solid method for luminescence enhancement. The structures of the as‐prepared samples agreed well with the standard phase of Sr3 (PO4 )2, even when Dy 3+ and Li + were introduced. Under ultraviolet excitation at 350 nm, the Sr3 (PO4 )2 :Dy 3+ sample exhibited two emission peaks at 483 nm and 580 nm, which were due to the 4 F9/2 → 6 H15/2 and 4 F9/2 → 6 H13/2 transitions of Dy 3+ ions, respectively. A white light was fabricated using these two emissions from the Sr3 (PO4 )2 :Dy 3+ phosphors. The luminescence properties of Sr3 (PO4 )2 :Dy 3+, Li + phosphors, including emission intensity and decay time, were improved remarkably with the addition of Li + as the charge compensator, which would promote their application in near‐ultraviolet excited white‐light‐emitting diodes.